HUBUNGAN ANTARA AKTIVITAS SHOLAT DENGAN TINGKAT KESEIMBANGAN STATIS PADA LANSIA PANTI SOSIAL TRESNA WERDHA BUDI MULIA 3 - Fahry Sannu Panthera (2022)
Elderly is a phase where a human being has entered the age of 60 years and is characterized by a decrease in his function and ability in physical and psychological aspects. Humans will live every day in proportion to the time that goes by. Balance is an important aspect of independent activities so that you can carry out activities safely without the risk of injury. Humans also live by religious principles, therefore someone who adheres to religion will worship. Prayer is a form of worship obligation that is commanded by Allah SWT in Islam for every servant. The purpose of this research is to find out whether there is a relationship between prayer activity and the level of static balance. The research design method used in this study is a cross-sectional study design. The measuring instrument used to measure the level of static balance is the One-Legged Stand test (OLST). Based on the results of the SPSS 25 data measurement with the Pearson Correlation test, the P value was p= .939. In conclusion, there is no significant relationship between prayer and the level of static balance.